Prevention of Corrupt Behavior with the Maqashid Syariah Approach - Dede Rosyada; Madian Muchlis; Popi Puadah; Ira Silviana Suseno (Green Publisher Indonesia, 2025)
This study aims to test the influence of religiosity, independence, professionalism, family resilience and remuneration as factors that affect corrupt behavior both partially and simultaneously so that efforts to prevent corrupt behavior through the Sharia Maqashid approach are obtained. The study used quantitative method, the population in this study is all employees in one agency that handles disasters. The sample size used was 269 respondents. The sampling technique used is Krijie Morgen. Based on the results of the study, it can be concluded that: (1) There is a significant influence partially or simultaneously between religiosity, independence, professionalism, family resilience and remuneration on corrupt behavior; (2) The application of